1996
DOI: 10.1002/pro.5560050319
|View full text |Cite
|
Sign up to set email alerts
|

A large compressibility change of protein induced by a single amino acid substitution

Abstract: The adiabatic compressibility (βs) was determined, by means of the precise sound velocity and density measurements, for a series of single amino acid substituted mutant enzymes of Escherichia coli dihydrofolate reductase (DHFR) and aspartate aminotransferase (AspAT). Interestingly, the βs values of both DHFR and AspAT were influenced markedly by the mutations at glycine‐121 and valine‐39, respectively, in which the magnitude of the change was proportional to the enzyme activity. This result demonstrates that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…The faster 'early responses', triggered as early as 400 femtoseconds, can be best described by the theory when impulse forces are used. Also, the sound speed estimated at 4-7 Å/ps in Mb is compared favorably with that in water (14 Å/ps) and concentration-dependent sound velocity in ~0.1 M protein solution (54,55). Furthermore, we identify several residues in Mb as 'disseminators' that propagate the signals faster than others and are found to be kinetically important to modulate gas molecule diffusion and rebinding (49,56).…”
Section: Introductionmentioning
confidence: 79%
“…The faster 'early responses', triggered as early as 400 femtoseconds, can be best described by the theory when impulse forces are used. Also, the sound speed estimated at 4-7 Å/ps in Mb is compared favorably with that in water (14 Å/ps) and concentration-dependent sound velocity in ~0.1 M protein solution (54,55). Furthermore, we identify several residues in Mb as 'disseminators' that propagate the signals faster than others and are found to be kinetically important to modulate gas molecule diffusion and rebinding (49,56).…”
Section: Introductionmentioning
confidence: 79%
“…A further clue to understanding both pressure and temperature stability was proposed by Gekko and co-workers. 43 On inspecting the effect of single amino acid substitutions on compressibility and thermodynamic stability of dihydrofolate reductase, they recently showed an inverse correlation between the two parameters. Because compressibility is also directly related to protein flexibility, 44 the creation of a void in the F31A mutant would result in increased flexibility, with concomitant decrease in both pressure and temperature stability of the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the adiabatic compressibility can reveal the structural characteristics of native proteins (27), conformational changes induced by ligand binding (29), reduction of disulfide bonds (30), and denaturation (31). Recent studies on various mutants of two E. coli proteins, dihydrofolate reductase (32) and aspartate aminotransferase (33), revealed that a perturbation as small as a single amino acid substitution induces large changes in adiabatic compressibility, demonstrating the sensitivity of this parameter that is comparable with the enzyme activity in response to structural perturbation.…”
mentioning
confidence: 99%